2022
DOI: 10.1002/ccr3.6074
|View full text |Cite
|
Sign up to set email alerts
|

Transient cortical blindness, a rare complication during cerebral digital subtraction angiography: A case report and literature review

Abstract: Transient cortical blindness (TCB) is a rare consequence of cerebral angiography with no recognized cause. TCB was observed in a patient with a wide‐neck cavernous aneurysm during digital subtraction angiography. One hour after angiography, vision returned spontaneously, with no neurological damage. An MRI was performed three hours after the incident and revealed no abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Desain penelitian yang digunakan adalah analitik dengan pendekatan cross sectional. Sumber data penelitian menggunakan data sekunder dari rekam medis pasien dengan status kasus terkonfirmasi COVID- 19…”
Section: Metodeunclassified
“…Desain penelitian yang digunakan adalah analitik dengan pendekatan cross sectional. Sumber data penelitian menggunakan data sekunder dari rekam medis pasien dengan status kasus terkonfirmasi COVID- 19…”
Section: Metodeunclassified
“…Atypical fndings of COVID-19 infections described in literature include pleural and pericardial efusions, calcifcations, pneumothorax, cavitation, lung collapse, mediastinal enlargement, and cardiomegaly [8][9][10][11]. Based on previous studies, chest CT features were shown to vary based on age of the patients, duration of symptom at presentation, COVID-19 vaccination status, and the strain of the virus [12][13][14][15]. A study done in Ghana had demonstrated that more patients in the second wave had evidence of COVID-19 disease on chest imaging than those patients in the frst wave [8].…”
Section: Introductionmentioning
confidence: 98%
“…Cortical blindness (CB) is a loss of vision in both eyes due to an occipital striate cortex injury [ 1 ]. In addition to congenital abnormalities, ischemic stroke, hypoxemia, trauma, and poisoning have all been documented as causes of CB [ 2 ]. CB is a rare complication after the vertebral artery interventional operation [ 3 ].…”
Section: Introduction and Importancementioning
confidence: 99%